IMPACT OF ARTIFICIAL INTELLIGENCE ON OCCUPATIONAL HEALTH AND SAFETY - A. S. CONSTANTIN; C. BORDA; C. LUCHIAN; E. BULBOACĂ; M. GHEORGHE; C. RADU (Fiabilitate şi Durabilitate)
The impact of artificial intelligence on worker well-being in occupational health and safety. The meteoric rise of artificial intelligence (AI) is reshaping work environments in various sectors. While AI presents undeniable potential for increasing efficiency and productivity, its influence on occupational health and safety (OHS) remains multidimensional and complex. This article examines the multiple ways in which AI can impact OSH, exploring both its potential benefits and inherent challenges. It advocates a comprehensive and nuanced approach to using AI to improve OSH. It underscores the critical need for robust regulations, ethical considerations, and ongoing human oversight to ensure that AI serves as a catalyst for positive change in the workplace, prioritizing both worker safety and overall well-being.